SISTEM MONITORING DAN PENYIRAMAN OTOMATIS TANAMAN SRIGADING (NYCTANTHES ARBOR-TRISTIS) BERBASIS IOT (INTERNET OF THINGS) DENGAN MENGGUNAKAN SENSOR KELEMBAPAN TANAH DAN SUHU RUANG PADA POT - Febriyansyah Ramadhan; Ita Rusmala Dewi (INFOTECH journal, 2024)
This automatic plant monitoring and watering system is designed to make it easier to manage plants around pots or indoors such as greenhouses. This tool uses two main sensors, namely the DHT11 sensor to detect temperature and the soil moisture sensor to measure soil moisture. The microcontroller used is NodeMCU ESP8266. The output of this system includes a mini water pump, DC fan, and the Blynk application on Android devices. Based on the tests that have been carried out, if the temperature is detected above 33ᵒC, the fan will activate; but if it is below 33ᵒC, the fan will turn off. When soil moisture is detected above 90ᵒC, the water pump will activate as it indicates dry soil. The Blynk app features 3 monitoring controls, including 2 LCD screens. The first LCD monitors indoor temperature, while the second LCD is used to monitor soil moisture and fan conditions. There is also a Gauge display which displays the condition of the soil moisture sensor embedded in the plant pot.